2019
DOI: 10.1177/1420326x19862009
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and mixing ratio selection of mixed liquid desiccant for a dehumidification system

Abstract: Liquid-desiccant dehumidification system in building air-conditioning has high energy efficiency in comparison to traditional dehumidification technology that needs to cool air below the dew point temperature. Since the dehumidification process dominates the performance of a liquid-desiccant system, this study aims to develop a deeper understanding in the dehumidification performance of some liquid desiccants. Then, an experiment test was conducted to determine the CaCl2-LiCl mixed liquid-desiccant system in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Jiang et al. 23 conducted experiments using mixing of liquid desiccants. LiCl and CaCl 2 mixed in the ratio 3:1 gave the best performance in terms of highest DE.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al. 23 conducted experiments using mixing of liquid desiccants. LiCl and CaCl 2 mixed in the ratio 3:1 gave the best performance in terms of highest DE.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of LiCl and CaCl 2 was used to reduce the cost of LiCl and to improve the dehumidification performance. 10,25 It was observed that the cost of the desiccant was reduced by 30% for the same moisture removal capacity and also regeneration cost was reduced by 29%. It was also observed that by adding both PVOH and LiCl to silica gel, its performance was improved by 55% consistently as its moisture removal capacity was improved significantly.…”
Section: -11mentioning
confidence: 97%
“…Temperature and humidity independent control system based on the liquid desiccant dehumidification is a useful energysaving system to satisfy temperature and humidity demand separately. [2][3][4] However, in traditional liquid desiccant dehumidification system, the liquid desiccant solutions such as lithium bromide solution (LiBr), lithium chloride solution (LiCl), and calcium chloride solution (CaCl 2 ) absorb water vapour from the wet air in a direct contact mode. As a result, the liquid droplet entrainment and air pollution often happen, and it can cause corrosion in the ventilating pipe and air pollution.…”
Section: Introductionmentioning
confidence: 99%